Transcription factor binding sites are genetic determinants of retroviral integration in the human genome. - Barbara Felice; Claudia Cattoglio; Davide Cittaro; Anna Testa; Annarita Miccio; Giuliana Ferrari; Lucilla Luzi; Alessandra Recchia; Fulvio Mavilio (PLoS ONE)
Gamma-retroviruses and lentiviruses integrate non-randomly in mammalian genomes, with specific preferences for active chromatin, promoters and regulatory regions. Gene transfer vectors derived from gamma-retroviruses target at high frequency genes involved in the control of growth, development and differentiation of the target cell, and may induce insertional tumors or pre-neoplastic clonal expansions in patients treated by gene therapy. The gene expression program of the target cell is apparently instrumental in directing gamma-retroviral integration, although the molecular basis of this phenomenon is poorly understood. We report a bioinformatic analysis of the distribution of transcription factor binding sites (TFBSs) flanking >4,000 integrated proviruses in human hematopoietic and non-hematopoietic cells. We show that gamma-retroviral, but not lentiviral vectors, integrate in genomic regions enriched in cell-type specific subsets of TFBSs, independently from their relative position with respect to genes and transcription start sites. Analysis of sequences flanking the integration sites of Moloney leukemia virus (MLV)- and human immunodeficiency virus (HIV)-derived vectors carrying mutations in their long terminal repeats (LTRs), and of HIV vectors packaged with an MLV integrase, indicates that the MLV integrase and LTR enhancer are the viral determinants of the selection of TFBS-rich regions in the genome. This study identifies TFBSs as differential genomic determinants of retroviral target site selection in the human genome, and suggests that transcription factors binding the LTR enhancer may synergize with the integrase in tethering retroviral pre-integration complexes to transcriptionally active regulatory regions. Our data indicate that gamma-retroviruses and lentiviruses have evolved dramatically different strategies to interact with the host cell chromatin, and predict a higher risk in using gamma-retroviral vs. lentiviral vectors for human gene therapy applications.